Intraclade Heterogeneity in Nitrogen Utilization by Marine Prokaryotes Revealed Using Stable Isotope Probing Coupled with Tag Sequencing (Tag-SIP) - Morando, Michael; Capone, Douglas G. (Frontiers in Microbiology, 2016)
Nitrogen can greatly influence the structure and productivity of microbial communities through its relative availability and form. However, roles of specific organisms in the uptake of different nitrogen species remain poorly characterized. Most studies seeking to identify agents of assimilation have been correlative, indirectly linking activity measurements (e.g., nitrate uptake) with the presence or absence of biological markers, particularly functional genes and their transcripts. Evidence is accumulating of previously underappreciated functional diversity in major microbial subpopulations, which may confer physiological advantages under certain environmental conditions leading to ecotype divergence. This microdiversity further complicates our view of genetic variation in environmental samples requiring the development of more targeted approaches. Here, next-generation tag sequencing was successfully coupled with stable isotope probing (Tag-SIP) to assess the ability of individual phylotypes to assimilate a particular N source. Our results provide the first direct evidence of nitrate utilization by organisms thought to lack the genes required for this process including the heterotrophic clades SAR11 and the Archaeal Marine Group II (MG-II). We also provide new direct evidence of in situ nitrate utilization by the cyanobacterium Prochlorococcus in support of recent findings. Furthermore, these results revealed widespread functional heterogeneity, i.e. different levels of N assimilation within clades, likely reflecting niche partitioning by ecotypes. The addition of nitrate utilization to ecosystem and ecosystem models by these globally dominant clades will likely improve the mechanistic accuracy of these models.